Between Worlds Understanding Ritual Cave Use in Later Prehistory - Büster, Lindsey; Warmenbol, Eugène; Mlekuž, Dimitrij (Springer International Publishing : Imprint: Springer, 2019)
The recent resurgence of academic interest in caves has demonstrated the central roles they played as arenas for ritual, ceremony and performance, and their importance within later prehistoric cosmologies. Caves represent very particular types of archaeological site and require novel approaches to their recording, interpretation and presentation. This is especially true in understanding the ritual use of caves, when the less tangible aspects of these environments would have been fundamental to the practices taking place within them. Between Worlds explores new theoretical frameworks that examine the agency of these enduring 'natural' places and the complex interplay between environment, taphonomy and human activity. It also showcases the application of innovative technologies, such as 3D laser-scanning and acoustic modelling, which provide new and exciting ways of capturing the experiential qualities of these enigmatic sites. Together, these developments offer more nuanced understandings of the role of caves in prehistoric ritual, and allow for more effective communication, management and presentation of cave archaeology to a wide range of audiences.